Examining classroom transformational spaces in developing student agency - Idrus, Faizah (2013)
Students are constructed agents in the classroom should they be given the chance to do so. This article reports the investigation that seeks to address the lack or the absence of student agency in the English language classrooms in the quest for a collaborative and dynamic student-teacher relationship. Fundamentally, this study attempts to examine the perceptions of teachers and students about classroom collaborations between students-student and student-teacher the English literature classrooms. It also seeks to identify how their collaborative acts can be suggestive to transforming a linear classroom lesson to a more vibrant and effective one and simultaneously develop a sense of agency among students. A qualitative inquiry employing semi-structured interviews, classroom observations and group interviews with 12 secondary English language school teachers and their student were conducted. I aspire to identify whether teachers’ classroom practices (and instructions) have any impact on students’ interactions with each other during task completion. Student interactions and collaboration could be the gateway to the construction of agency. The preliminary results pointed a finger to teachers’ reluctance to relinquish their authority and power to students for various reasons. Teachers, more than students felt that their authoritative figure were one of the key indicators of classroom progress in a result-driven education system. The results obtained aim to be informative in pointing to the viability of providing avenues for students to develop their agency with teachers’ support and encouragement via transformational learning spaces.